FORMULASI KODE ETIK PENDIDIK DALAM PERSPEKTIF PENDIDIKAN ISLAM - Farhan, Moh. (Universitas Islam Sultan Agung, 2018)
BeingÂ EducatorÂ is an honour profession in Islam. It is an essensial factor in the education system. Thus a dignityÂ and an authority of this profession have to be maintained by the educators. The way to keep the honour of this profession can be done by conductingÂ ethical codes as a guidence to conduct activities as the educators.In a modern era, an educator ethic has been formulated. However, it shows unoptimal to keep the educatorsâ€™ dignity. Thus, a solution is needed to solve the problem. Part of the solutionÂ from Islamic education scholars during Islamic education hystory is the genuin thinking of those scholars.Â They have formulated the educatorâ€™s ethics codes. From their thinking and ideas, there are three ethic codes that can be understood: The First:Â related to the obligation to have a good intention as the educator by improving a quality ofÂ â€œtaqwaâ€ to Allah SWT because teaching is a worship. The second:Â the educators have to keep theirÂ profession by improving the personality with a good character (Akhlak). The third,Â keep improving the educatorsâ€™ competences and professionalism.